Experimental and numerical implementation of auxetic substrate for enhancing voltage of piezoelectric sandwich beam harvester. Issue 27 (14th December 2022) - Fatahi, Mohamad Hossein; Hamedi, Mohsen; Safarabadi, Majid
Abstract: To harvest energy from environment vibration, it is a good way to use piezoelectric material as a generator that converts mechanical strain to electrical charge. This paper aims to develop a numerical model to predict the performance of piezoelectric energy harvester in beam configuration in accordance to experimental test and then study the effect of implementing auxetic substrate. Two beams are manufactured using isotropic and auxetic substrates. Implementing auxetic substrate excites piezo in both in-plane directions leading to generate more charge while equivalent stress remains constant. Modal test and frequency sweep are done for these two types of beams. For updating the model, mechanical and coupling properties of components in beam studied and more effective parameters are selected and participated in optimization. Genetic algorithm is used for optimization and converged after seven generations. The updated model has maximum 1.6% error in natural frequency and 5.6% in voltage. With a fine adjustment of beam dimensions, natural frequencies are set to 50 Hz and performance of two beams are compared. With same amount of piezo material and same stress applied on, a 30% improvement on output voltage is observed.